1992
DOI: 10.1002/iroh.19920770309
|View full text |Cite
|
Sign up to set email alerts
|

Metacyclops minutus (CLAUS, 1863) ‐ Population Dynamics and Life History Characteristics of a Rapidly Developing Copepod

Abstract: The cyclopoid copepod Metacyclops minutus, a typical species of temporary pools, shows an unusual life cycle in a small pond in South Germany. The species is present from April/May to December during which period it forms at least 8 generations. Winter and early spring, when the pond is frozen to the bottom, are spent in the bottom mud as C4 or C5 instars. M. minutus shows an extraordinarily low degree of sex size dimorphism (female: male body length ratio) and no significant differences in. copepodite develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…In particular, we found Metacyclops minutus to emerge in significantly higher numbers from the propagule bank of the agriculturally modified stream section. This species is a successful colonist of highly ephemeral waterbodies with an exceptionally short life cycle of about a week (Maier, 1992;. In previous studies in ponds of Doñana, it was found in the smallest, most short-lived ponds (Serrano & Fahd, 2005), and in salinities up to 28 mS cm -1 , or a combination of both (Frisch et al, 2006;.…”
Section: Discussionmentioning
confidence: 96%
“…In particular, we found Metacyclops minutus to emerge in significantly higher numbers from the propagule bank of the agriculturally modified stream section. This species is a successful colonist of highly ephemeral waterbodies with an exceptionally short life cycle of about a week (Maier, 1992;. In previous studies in ponds of Doñana, it was found in the smallest, most short-lived ponds (Serrano & Fahd, 2005), and in salinities up to 28 mS cm -1 , or a combination of both (Frisch et al, 2006;.…”
Section: Discussionmentioning
confidence: 96%
“…The most spectacular example is the cyclopoid Metacyclops minutus, which in tiny ponds in Germany may pass through 8 or more generations in a single growing season. Under natural conditions they may develop from egg to adult in 4.7-8.6 days, and in 218 the laboratory have matured in as little as 4 days at 30 °C (Maier, 1992). In this species also, males differ little from females in size, females and males mature at about the same rate, and adults and subadults may pass through dry phases in a state of quiescence, and through the winter in diapause (Maier, 1992).…”
Section: Discussionmentioning
confidence: 97%
“…strenuus Fischer, 1851, and Macrocyclops albidus. Some examples of species collected from road ruts include Canthocamptus australicus (Sars, 1908) in Australia (Hamond, 1988), Mesocyclops leuckarti (probably = M. aspericornis) in Guam (Watkins & Belk, 1975), and Metacyclops minutus (Claus, 1863) and several other species by Maier (1992Maier ( , 1998 and Maier et al (1998). Even footprints may serve as copepod microhabitats: Brehm (mentioned in Gurney, 1933: 221) found Diacyclops bicuspidatus (Claus, 1857) in the small pools formed by his own footprints in spongy woodland soil.…”
Section: Human-modified or Artificial Habitatsmentioning
confidence: 99%
“…the sexual size dimorphism) (cf. DeFrenza et al, 1986;Grad & Maly, 1988, 1992. Males which are small in relation to their females (generally the males of large sized species; Fig.…”
Section: Discussionmentioning
confidence: 99%